Gender Diversity and Cash Holdings in Indonesia Non-Financial Firms - Dwijayanti, S. Patricia Febrina; Wijaya, Hendra (Studi Akuntansi dan Keuangan Indonesia, 2023)
This study aimed to investigate the effect of gender diversity on the board of commissioners and the board of directors on the company's cash holdings. A non-financial firm with 1305 observations that was listed on the Indonesia Stock Exchange between 2015 and 2019 serves as the study’s sample. The data in this study were analyzed using multiple regression. The ratios of cash holdings to net assets and total assets are used to calculate the amount of cash held. According to this study, the company’s cash holdings are negatively impacted by the diversity of the board of commissioners, and positively by the diversity of the board of directors